Pengaruh Pelayanan Pelanggan dan Inovasi Produk terhadap Kepuasan Pelanggan di Resto Mie Gacoan Jatiasih - Dwi Mahdi Mahesa; Natal Indra (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2025)
This study aims to analyze the influence of customer service and product innovation on customer satisfaction at Resto Mie Gacoan. Using a quantitative method with an associative approach, data were collected through questionnaires distributed to 40 active customers. Analysis techniques included validity and reliability tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²) using SPSS. The results show that product innovation has a relatively more significant influence on customer satisfaction than customer service, though its significance value slightly exceeds 0.05. Customer service does not have a statistically significant effect. Simultaneously, both variables do not significantly influence customer satisfaction. However, the R² value of 12.6% indicates that service and product innovation still contribute to variations in satisfaction, with the rest influenced by other factors not included in the model. These findings suggest that product innovation plays a more crucial role in enhancing satisfaction at Resto Mie Gacoan. Therefore, management is encouraged to prioritize innovative menu development and unique customer experiences in their marketing strategies.